PENGARUH PENGETAHUAN DAN KELELAHAN KERJA TERHADAP UNSAFE ACTION PADA PEKERJA OPERASIONAL KALLA TRANSPORT & LOGISTIK - Labibah, Iffat Nurjihan; Amelia AP, A. Rizki; Muchlis, Nurmiati (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2023)
Unsafe behaviors can endanger people or workers and are caused by internal factors such as worker knowledge or fatigue. The study used a quantitative method with a cross-sectional approach with 51 respondents. Data were collected by questionnaire and analyzed using univariate and bivariate tests with a confidence level of α = 0.05. The binary logistic regression test results show that work fatigue is the variable that significantly influences risky behavior (p-value 0.019). The Exp(B) for job fatigue is 5,348, indicating that fatigue has a five times greater impact on risky behavior than knowledge does.